EXPERIENCE OF TREATMENT OF A PATIENT WITH POSTOPERATIVE PERINEAL HERNIA (CLINICAL CASE) - Ооржак, Орлан Валерийович; Топаков, Евгений Валерьевич; Лишов, Евгений Владимирович; Постников, Дмитрий Геннадьевич; Шост, Сергей Юрьевич; Довбета, Евгений Владимирович; Харитонов, Александр Андреевич; Мироненко, Татьяна Владимировна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; et al. (Medicine in Kuzbass, 2023)
Postoperative perineal hernias (PPG) differ in nature from «classic» pelvic hernias. The occurrence of PPG is largely due to the violation of the integrity of the myofascial structures of the pelvic floor due to surgery and their replacement with scar tissue. There is an annual increase in the number of patients with rectal cancer in the world, they occupy the 7th place in the structure of malignant neoplasms. When cancer is localized in the lower ampullary rectum, the main method of surgery is abdominal-perineal extirpation. According to the literature, the incidence of perineal hernia after abdominal-perineal extirpation of the rectum is in the range from 0.6 % to 37 %. This article describes a rare clinical case of postopretionary hernia of the perineum. Taking into account the optimal chosen surgical management tactics of the patient, a favorable outcome was obtained for the woman.